Аналіз температурного поля у твердосплавному різці в процесі його індукційного паяння та неізотермічного гартування - Дутка, В.А.; Майстренко, А.Л.; Колодніцький, В.М.; Лукаш, В.А.; Вировець, Л.М. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2007)
The results of numerical investigation of temperature field in cutters with the hard-alloy inserts during three stages of thermal treatment – induction soldering, cooling in air and hardening in liquid medium are presented. The inductor configuration for induction soldering and creation temperature field for hardening is obtained. The numerical simulation of temperature field in cutter body during hardening-process for two cases of choice of the hardening compound is considered: 1 case – water solution of salt and alkali, and 2 case – liquid nitre. It is shown, that in two cases the temperature fields in steel cutter body are analogous in the same time moments in begin of hardening- process. It follows that in two cases in the same time moments in begin of hardening-process the analogous structural transformation will occur. Bat with time the analogy of temperature fields in steel cutter body in two cases of hardening disappears.